A case report of ineffective electroconvulsive therapy for chronic pain - Takashi Fukao; Masaki Fujiwara; Yuto Yamada; Kazushi Asada; Takahiro Asada; Hirotoshi Ri; Shinji Sakamoto; Manabu Takaki (PCN Reports)
Abstract Background Somatic symptom disorder (SSD), which includes chronic pain, is a common mental disorder characterized by significant functional impairment and other psychiatric comorbidities. Electroconvulsive therapy (ECT) has been proposed as a potential treatment for refractory chronic pain. However, evidence supporting its efficacy is limited and/or low quality. We present a case of SSD with chronic pain in which ECT was ineffective. Case Presentation The patient was a 63‐year‐old man with chronic pain in the lower back, buttocks, thighs, and soles of the feet. The duration of his chronic pain was 3.8 years. He was diagnosed with Bertolotti's syndrome and SSD. He did not meet the criteria for major depressive disorder. He kept physically active by walking and doing exercises to distract himself from his pain. He strongly perceived pain as a physical issue and preferred ECT over psychotherapy. Despite undergoing 10 ECT sessions with adequate seizures, his pain persisted. After four sessions, he experienced despair over the lack of improvement in pain, which temporarily intensified his suicidal ideation. After undergoing ECT, he continued to maintain his activities, including walking and exercise, while his catastrophic thinking about pain persisted. Conclusion The ineffectiveness of ECT in this case highlights the need for balanced counseling, particularly for patients who consider ECT a last‐resort treatment. Psychological monitoring and depression screening are essential, especially given the risk of heightened despair or suicidal ideation when ECT is ineffective. Therefore, collaborative decision‐making based on accurate information is vital.